What drives exchange rates? New evidence from a panel of US dollar bilateral exchange rates - Jean-Philippe Cayen; Donald Coletti; René Lalonde; Philipp Maier (Bank of Canada, 2010)
We use a novel approach to identify economic developments that drive exchange rates in the long run. Using a panel of six quarterly U.S. bilateral real exchange rates Australia, Canada, the euro, Japan, New Zealand and the United Kingdom over the 1980-2007 period, a dynamic factor model points to two common factors. The first factor is driven by U.S. shocks, and cointegration analysis points to a long-run statistical relationship with the U.S. debt-to-GDP ratio, relative to all other countries in our sample. The second common factor is driven by commodity prices. Incorporating these relationships directly into a state-space model, we find highly significant coefficients. Then, we decompose the historical variation of each exchange rate into U.S. shocks, commodities, and a domestic component. We find a strong role for economic fundamentals: Changes in the two common factors, which are driven by the (relative) U.S. debt-to-GDP ratio and commodity prices, can explain between 36 and 96 per cent of individual countries' exchange rates in our panel.
Keywords: J31; 330; Exchange rates; Econometric and statistical methods; Wechselkurs; Öffentliche Schulden; Volkswirtschaft; US-Dollar; Australien; Kanada; Neuseeland; Großbritannien; Europäische Wirtschafts- und Währungsunion; Japan